Future nutrient recovery from sewage sludge regarding three different scenarios - German case study. (20th January 2022) - Sichler, Theresa Constanze; Adam, Christian; Montag, David; Barjenbruch, Matthias
Abstract: Agricultural sewage sludge utilization becomes less important in Germany. In 2017, new fertilizer and waste laws caused the agricultural sewage sludge utilization to collapse by more than a quarter. From 2029, German wastewater treatment plants (WWTPs) must recover phosphorus (P) from sewage sludge if it contains more than 2 wt % P. Agricultural utilization will be prohibited for large WWTPs >100, 000 population equivalents (pe) from 2029 and > 50, 000 pe from 2032. In Germany, each federal state must annually report amounts and quality of agriculturally utilized sewage sludge which was 16% of the total disposal in 2019. The reports of 10 states were evaluated for 2016 and 2017 representing approx. 60% of the total agriculturally used sludge volume. In 2016, 60% of the WWTPs' sludges exceeded the recovery limit of 2 wt % P which is 70% of the amount of sludge and 85% of the phosphorus load. Other nutrients are not affected by the recovery obligation. However, many P recovery processes recover other nutrients, too. Considering three different scenarios for future German sewage sludge disposal shows that 70–77% of the P load in sewage sludge will probably be recovered in the future. At the same time, this applies for about 0–16% nitrogen, 36–52% of calcium, 31–53% of potassium, and 40–52% of magnesium. However, these recovered nutrients loads can substitute only 1% or less of the commercial fertilizer demand except from phosphorus which is up to 43% of the demand. Graphical abstract: Image 1 Highlights: From 2029, phosphorus (P) recovery is obligatory for sludges with more than 2% P. P contents in sewage sludge rise with the wastewater treatment plant (WWTP) size. According to evaluated data, 40% of the German WWTPs fall below this 2% P limit. Future German P recovery (>70%) could substitute 44% of the mineral fertilizers. Lost nutrient potentials apart from P are low (<1%) compared to the demand.